Stabilisation and reactivity studies of donor-base ligand-supported gallium-phosphides with stronger binding energy: a theoretical approach. Issue 12 (8th March 2023) - Francis, Maria; Roy, Sudipta
Abstract : Gallium phosphide is a three-dimensional polymeric material of hetero-diatomic GaP unit. Our studies reveal the synthetic viability of donor base-stabilised monomeric Ga–P compounds with stronger binding energy, and explore their reactivity with metal carbonyls. Abstract : Gallium phosphide is a three-dimensional polymeric material of the hetero-diatomic GaP unit, which has a wurtzite type structure, and captivating application as a light emitting diode (LED). As a result, there is a constant search for suitable precursors to synthesise GaP-based materials. However, the corresponding monomeric species is exotic in nature due to the expected GaP multiple bond. Herein, we report on the theoretical studies of stability, chemical bonding, and reactivity of the monomeric gallium phosphides with two donor base ligands having tuneable binding energies. We have performed detailed investigations using density functional theory at three different levels (BP86/def2-TZVPP, B3LYP/def2-TZVPP, M06-2X/def2-TZVPP), QTAIM and EDA-NOCV (BP86-D3(BJ)/TZ2P, M06-2X/TZ2P) to analyse various ligand-stabilised GaP monomers, which revealed the synthetic viability of such species in the presence of stable singlet carbenes, e.g., cAAC, and NHC as ligands [cAAC = cyclic alkyl(amino) carbene, NHC = N-heterocyclic carbene] due to the larger bond dissociation energy compared to a phosphine ligand (PMe3 ). The calculated bond dissociation energies between a pair of ligands and the monomeric GaP unit are found to be in the range of 87 to 137 kcal mol −1, predicting their possible syntheses in the laboratory. Further, the reactivity of such species with metal carbonyls [Fe(CO)4, and Ni(CO)3 ] have been theoretically investigated.